2017
DOI: 10.3390/nu9040331
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Resistant-Starch (ERS) Diet Shapes Colon Microbiota Profile in Parallel with the Retardation of Tumor Growth in In Vitro and In Vivo Pancreatic Cancer Models

Abstract: Background/aims: Pancreatic cancer (PC) is ranked as the fourth leading cause of cancer-related deaths worldwide. Despite recent advances in treatment options, a modest impact on the outcome of the disease is observed so far. We have previously demonstrated that short-term fasting cycles have the potential to improve the efficacy of chemotherapy against PC. The aim of this study was to assess the effect of an engineered resistant-starch (ERS) mimicking diet on the growth of cancer cell lines in vitro, on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 60 publications
(88 reference statements)
1
47
0
Order By: Relevance
“…A further strategy to decrease glucose levels has been the development of engineered diets replacing corn starch with resistant starch, which is not digestible by the intestinal enzymes thus not releasing glucose. This approach has turned out to slow pancreatic cancer growth in a mouse model, without causing weight loss (16). Consistently, a number of previous studies on rat models of colon cancer revealed a protective role for resistant starch against carcinogenesis (17)(18)(19)(20), even upon high-protein diets (19,20).…”
Section: A New Food Culture Based On Limiting Dietary Surplus and Onsupporting
confidence: 54%
See 2 more Smart Citations
“…A further strategy to decrease glucose levels has been the development of engineered diets replacing corn starch with resistant starch, which is not digestible by the intestinal enzymes thus not releasing glucose. This approach has turned out to slow pancreatic cancer growth in a mouse model, without causing weight loss (16). Consistently, a number of previous studies on rat models of colon cancer revealed a protective role for resistant starch against carcinogenesis (17)(18)(19)(20), even upon high-protein diets (19,20).…”
Section: A New Food Culture Based On Limiting Dietary Surplus and Onsupporting
confidence: 54%
“…It has been demonstrated that certain types of foods selectively enhance some microbial groups which in turn can shape the profile of the whole gut microbiota thus affecting the onset and the progression of several diseases, including cancer. Fiber-rich food regimens significantly decrease pro-inflammatory microorganisms such as Bacteroides acidifaciens, Escherichia coli, Ruminococcus gnavus and Clostridium cocleatum (16), supporting the indication that engineered diets able to perturb gut microbial community can be synergistically used together with the current chemotherapeutic approaches. Administration of probiotics and prebiotics represents the most common measure to shape gut microbiota in order to slow cancer progression, improve response to therapy or limit toxic side effects (22).…”
Section: A New Food Culture Based On Limiting Dietary Surplus and Onmentioning
confidence: 79%
See 1 more Smart Citation
“…A considerable proportion of nonantibiotics also influence the growth of bacterial species [18]. A resistant starch diet promoted a decrease in tumor progression in PDAC xenograft mice, which was associated with a reduction in proinflammatory fecal microbiota [19].…”
Section: Therapeutic Dilemma Of Pancreatic Cancermentioning
confidence: 99%
“…In this case, the environment becomes undesirable for pathogenic microorganisms, and consequently reduces the risk of cancer cell formation (Khalili & Amini, 2015). Some studies have shown that resistant starch can prevent colorectal cancer (Panebianco et al, 2017;Yin & Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%